Revealing the Structure Evolution of Heterogeneous Pd Catalyst in Suzuki Reaction via the Identical Location Transmission Electron Microscopy - Shi, Wen; Niu, Yiming; Li, Shunlin; Zhang, Liyun; Zhang, Ying; Botton, Gianluigi A; Wan, Ying; Zhang, Bingsen (ACS nano, 2021)
The mechanism of palladium nanoparticles (Pd NPs)-catalyzed cross-coupling reactions has been the subject of intense debate since the recognition of catalytic active sites involving a wide array of dynamic changed Pd species. Here, through the combination of the hot filtration experiment together with the recently developed identical location transmission electron microscopy (IL-TEM) method, the delicate structure evolution of highly dispersed Pd NPs supported on oxygen-functionalized carbon nanotubes (Pd/oCNTs) as well as the kinetics properties of derived dissolved species in liquid phase were systemically investigated in the Suzuki–Miyaura reaction. The result indicates that the leached Pd components caused by the strong adsorption of reactants might have a significant contribution to the coupling products, and the degree for different substrates follows the order of iodobenzene > phenylboronic acid > bromobenzene. Meanwhile, the typical three sequential behaviors of supported Pd NPs, including dissolution, deposition, and growth, along with the increase of the conversion throughout the reaction were spatiotemporally observed by tracking the evolution of individually identifiable NPs. The performed work not only provides direct evidence for the interaction between Pd NPs surface with reactants on atomic scale but also gives a valuable reference for fundamentally understanding the mechanism of the heterogeneous Pd-catalyzed Suzuki coupling process as well as rational design of next-generation catalysts with high efficiency and reusability for synthetic applications.